Appraising the Interpretation of the Word 'Scientist' under the Special Residence Requirements for Australian Citizenship. (9th September 2020) - Owoeye, Olasupo
Abstract: The article examines the interpretation of the word 'scientist' under Instrument IMMI 13/056 made pursuant to section 22B(1) of the Citizenship Act. The article considers the literal interpretation of the word scientist and the objective of the Instrument. The article provides a critique of the cases that have gone to the Australian Administrative Appeals Tribunal and argues that the interpretation favoured by the Tribunal is misconceived. The article contends that the Tribunal seems to be giving undue support to an arbitrary or haphazardly serendipitous exercise of ministerial power under the special residence framework in a manner that runs afoul of the tenour of section 22B(1) of the Citizenship Act.